How high can trumpet moths occur: documentation of mountainous leaf-mining Tischeriidae, featuring a species from record-high elevations - Stonis, Jonas R.; Diškus, Arūnas; Remeikis, Andrius; Orlovskytė, Svetlana; Katinas, Liliana (Zootaxa, 2024)
This publication describes four new high-altitude species of Tischeriidae, all within the genus Astrotischeria Puplesis & Diškus: A. peruanica Diškus & Stonis, sp. nov., A. montivaga Diškus & Stonis, sp. nov., A. viscacha Diškus & Stonis, sp. nov., and A. andina Diškus & Stonis, sp. nov. Notably, A. andina sp. nov., is the highest-recorded Tischeriidae species, documented at an elevation of 3,600 meters, the highest altitude recorded for the family worldwide to date. The study also provides a summary of current species distribution data, indicating that species from altitudes up to 2,000 meters are predominant, with high-elevation species above 3,000 m comprising about 5% in the tropics and 2% globally. It is hypothesized that there is a high probability of discovering more high-elevation Tischeriidae within the genus Astrotischeria, particularly those feeding on Baccharis L. in the Andes, South America. Additionally, a new elevation record for the mountainous species Astrotischeria parapallens Diškus & Stonis is documented. The article is illustrated with 63 figures, including photographs of the adults, male and female genitalia, leaf mines and their habitats, a molecular topology, and graphics depicting trends in Tischeriidae occurrence across different elevations.